Arte tigua como medio de expresión cultural para rescatar la iconografía y las costumbres del cantón El Guabo - Sánchez Brito, Mónica Alexandra (2018)
The following research text, tries to highlight an artistic proposal to rescue the iconography and customs of the canton of El Guabo through the Tigua art style as a means of cultural expression, this pictorial trend is related to naive art because they are they characterize by their thematic expressing in their specifically thematic works such as celebrations, typical foods and their productive activities. This indigenous pictorial style emerges in the province of Cotopaxi in the Tigua region, this pictorial tendency was mainly used to highlight its customs through painting; this style used as a drum support which were traditional in each festival, it began to shape the customs of the people as people working or celebrating a holiday, etc ... As Gómez mentions, due to the painting, it has been possible to commemorate "all beliefs, rites, legends, customs, ancestral knowledge, etc., shared by a group of people from a community, social sector or region "(Gomez, 2002), thanks to this art form, the identity of the community has been rescued. Painting has contributed to the customs of this town are not forgotten or devalued by new generations as this style has become a tradition for the inhabitants of the community, determining this style as a reference to rescue customs. In view of the community's lack of interest in maintaining customs, the three main factors that influence this problem have been determined. One of the specific factors is the globalization this failure has caused that over the years, the new generations ignore the roots of their community causing their devaluation. Education is another important aspect since from education to new generations a new educational style has been established, ignoring the teaching of ancient customs and, finally, migration is the determining factor since this has led to the adoption of new customs causing the identity of the community to be lost. Before this research it was established that through painting and images a greater retentive effect is achieved since the images communicate. As Arnheim tells us, "In the great works of art, the deepest meaning is transmitted to the view in a powerfully direct way by the perceptual characteristics of the compositional scheme". (Arnheim, 2007, page 464) The methodology used in this research is the iconographic method used by Panofsky, in which "it refers to the elements that accompany it, the attributes and characteristics of the work". (Armendariz, Sosa, & Puca, 2013, page 31) .Determining that through this method you can analyze the characteristics of the work, thus allowing the assessment of the work as part of a heritage legacy for future generations. The pictorial work "Footprints", will consist of four scenes in which the lost customs of the canton Guabo will be reflected, this work is made up of the traditional frame and the three remaining supports will be in circular form of several dimensions this circular frame is traditional in the canton, the three circular supports will be suspended from a transparent thin nylon, emphasizing that the identity of the Guabeña community is about to be forgotten, this work aims to cause an effect of remembrance on the spectators. Establishing painting as the most ideal and determining means, to meet the objectives of this research.